A contribution to the knowledge of the spider fauna of the wider Haloze region (northeast Slovenia) - Rok Kostanjšek (Natura Sloveniae)
A list of spider species collected in the wider Haloze region during the summer of 2002 is given. Altogether, 76 species belonging to 54 genera and 22 families were recorded at 43 localities, representing the first comprehensive spider list of Haloze. Dipoena braccata (Theridiidae) and Scotophaeus scutulatus (Ganphosidae) are new records for the Slovenian fauna. In addition, the water spider (Argyroneta aquatica), a vulnerable species in Slovenia, was found in one of the Drava River branches.